Design and Validation of a Modular Control Platform for a Voltage Source Inverter. (March 2023) - Lezcano, Hernan; Rodas, Jorge; Pacher, Julio; Ayala, Magno; Romero, Carlos
Abstract: Integrating renewable energies, such as wind or photovoltaic, requires an electronic power converter, the three-phase Voltage Source Inverter (VSI) the most common for such function. This paper presents a modular design of signal acquisition and control hardware (current and voltage) for the commercial SEMIKRON SKS35F VSI converter and a Texas Instruments TMS320F28335 DSP. Consequently, the proposed modular and open-source design allows its application in control systems of a VSI converter for isolated or grid-connected systems, applied to power generation based on renewable sources. The proposed scheme allows for a personalised design since it uses an open architecture to implement its own control algorithms that allow it to adapt to the application's particular needs, unlike closed-architecture commercial equipment. Detailed electronic printed circuit board designs for implementation are shown on paper. Finally, the experimental tests' results that validate the proposed design's correct functioning are presented.